Enhancing X-ray generation from twisted multilayer van der Waals materials by shaping electron wavepackets - Wong, Wesley Lee Wei (2024)
We study twisted bilayer van der Waals (vdW) materials as a platform to generate versatile bremsstrahlung X-rays, and show that the twist angle in bilayer vdW materials provides an unprecedented degree of controllability over various properties of bremsstrahlung radiation from these materials. Specifically, we combine the waveshaping of the free electron’s quantum wavepacket with the unique crystalline atomic positioning of twisted bilayers to realize shaped bremsstrahlung Xrays, which feature enhancements in directionality and intensity. In the process, we present a theoretical model for bremsstrahlung radiation that is applicable to twisted multilayer vdW materials in general. We also investigate the dependence of our X-ray emission mechanism on physical parameters, including the interlayer spacing and number of layers. Our findings pave the way for the use of twisted multilayer van der Waals materials in the generation of tailored X-ray spectra for applications like X-ray imaging, X-ray fluorescence, and X-ray treatment.